Abdullah Effendi al-Bosnawi (d. 1054/1644) and his Treatise Sirr al-yaqin - Ali Akbar Ziaee; Zahra KadkhudÁi Mizriji (حکمت اسرا, 2010)
AbdullÁh Effendi al-Bosnawi was a 17th century mystic who was greatly influential in the proliferation of Islamic culture in the Balkans. He composed many works in the field of theoretical mysticism, the most important of them being his commentary on the FuÒÙÒ al-Îikam of Ibn ÝArabÐ. In his treatise Sirr al-yaqÐn he sets out to comment on the verse “and worship your Lord until certainty comes to you” (15:99), and in the process touches on the station of AÎmadÐ and the meaning of yaqÐn. Rejecting the interpretation that yaqÐn signifies ‘death’, and basing himself on the words of Shaykh BakalinjÁr in JÁmi’s Manaqib al-Árifin, he takes yaqin to mean ‘the intuitive witnessing of the pre-eternal object’. The article in hand contains some explanations about the author of the treatise along with the original text of the treatise.